National self-identification of students of the Faculty of Orthodox Theology at the University of Warsaw (late 1920s-1930s) - Starodub, Andriy (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the article, the data about national structure of students of Faculty of Orthodox Theology of the University of Warsaw in the late1920s-1930s is analyzed. The features of national self-identification of different groups of students are designated. Conclusions are made about the reasons for the disproportionate representation among future theologians of persons self-identifying as Russian and Orthodox Poles.
Keywords: Second Polish Republic; national minority; Orthodox theology; the University of Warsaw